The Art of Science Communication—A Novel Approach to Science Communication Training - Susanna Greer (American Society for Microbiology, 2018)
Effective communication is a requisite skill for scientists. However, formalized training in this area is often unavailable for members of the scientific community. As one approach to combat this problem, the American Society for Biochemistry and Molecular Biology (ASBMB) developed The Art of Science Communication, an eight-week-long online course that provides facilitated instruction on how to communicate science in an oral format. The course is offered three times a year, and as of December 2017, nearly 200 individuals from all career stages have taken part in it. The course completion rate is currently 60%, a rate three to five times as high as the average for similar Massive Open Online Courses (MOOCs). Participants have indicated that taking the course has improved their ability to communicate about their research, and that the skills and lessons learned have benefited them professionally. Moving forward, we are examining approaches that will help us improve the course and expand its reach throughout the scientific community. This article details the development of the course and examines the role and potential of such training within the larger scientific community.